2015
DOI: 10.18600/toj.010107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Using Knee Savers on Lower Extremity Kinematics in Male Collegiate Baseball Catchers During Squatting

Abstract: Introduction:Baseball catchers often experience knee discomfort and pain, which are commonly attributed to prolonged deep squatting. Only one device on the market, knee savers, is described in its advertisements as able to decrease stress and discomfort in catchers' knees. Methods: We evaluated kinematic effects that knee savers have on the lower extremities during male collegiate baseball catchers' squats. Results: We found no significant differences in knee flexion angle during squatting with and without the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Several examples were observed wherein the inclusion of an intervention indeed reduced MSD risk caused by extreme posture by lessening the peak angle during that condition, which was different than what was observed in the previously KS studies (Gray et al, 2015;Stone et al, 2014a;Stone et al, 2017;Stone et al, 2014b). For example, knee flexion angle was about the same for all three sloped conditions, however the presence of a single intervention-KP or KS-caused a reduction in deep knee flexion during resting compared to no intervention.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Several examples were observed wherein the inclusion of an intervention indeed reduced MSD risk caused by extreme posture by lessening the peak angle during that condition, which was different than what was observed in the previously KS studies (Gray et al, 2015;Stone et al, 2014a;Stone et al, 2017;Stone et al, 2014b). For example, knee flexion angle was about the same for all three sloped conditions, however the presence of a single intervention-KP or KS-caused a reduction in deep knee flexion during resting compared to no intervention.…”
Section: Discussionmentioning
confidence: 67%
“…These studies did not find any significant change in lower extremity sagittal plane knee kinematics with and without the KS. Another study compared deep and shallow flexing baseball catchers and indicated that the use of KS will decrease knee flexion in deep flexing catchers, albeit not statistically significantly (Gray et al, 2015). On the surface, it might seem KS would not be a beneficial intervention for any work place environment which uses kneeling, however, there are several things to consider.…”
Section: Introductionmentioning
confidence: 99%